Squamous cell carcinoma and Merkel-cell carcinoma. Diagnostic and therapeutic recommendations of the Polish Dermatological Society - Lesiak, Aleksandra; Czuwara, Joanna; Kamińska-Winciorek, Grażyna; Kiprian, Dorota; Maj, Joanna; Owczarek, Witold; Placek, Waldemar; Rudnicka, Lidia; Rutkowski, Piotr; Sobjanek, Michał; Sokołowska-Wojdyło, Małgorzata; Szepietowski, Jacek; et al. (Dermatology Review/Przegląd Dermatologiczny, 2019)
The clinical, pathological and dermoscopic features, including recommended diagnostic procedures for cutaneous squamous cell carcinoma (SCC) and Merkel cell carcinoma (MCC) are presented. The therapeutic standard for both cancers is surgical removal. In the case of SCC Mohs microsurgery may be performed, with the intraoperative analysis of the completeness of excision. The recommendations also include non-surgical methods of treatment, including systemic therapies used in advanced forms of the disease. The aim of the recommendations is to provide help in choosing the optimal diagnostic and therapeutic options for individual patients with SCC or MCC. These recommendations take into consideration similar documents published by other scientific organizations and expert opinions of the authors.